Intra-specific Niche Partitioning in Antarctic Fur Seals, Arctocephalus gazella - Kayleigh A. Jones (Nature Portfolio, 2020)
Abstract Competition for resources within a population can lead to niche partitioning between sexes, throughout ontogeny and among individuals, allowing con-specifics to co-exist. We aimed to quantify such partitioning in Antarctic fur seals, Arctocephalus gazella, breeding at South Georgia, which hosts ~95% of the world’s population. Whiskers were collected from 20 adult males and 20 adult females and stable isotope ratios were quantified every 5 mm along the length of each whisker. Nitrogen isotope ratios (δ15N) were used as proxies for trophic position and carbon isotope ratios (δ13C) indicated foraging habitat. Sexual segregation was evident: δ13C values were significantly lower in males than females, indicating males spent more time foraging south of the Polar Front in maritime Antarctica. In males δ13C values declined with age, suggesting males spent more time foraging south throughout ontogeny. In females δ13C values revealed two main foraging strategies: 70% of females spent most time foraging south of the Polar Front and had similar δ15N values to males, while 30% of females spent most time foraging north of the Polar Front and had significantly higher δ15N values. This niche partitioning may relax competition and ultimately elevate population carrying capacity with implications for ecology, evolution and conservation.